Unités polylexicales dans le cadre du syntagme nominal - Sliwa, Dorota (Verbum – Analecta Neolatina, 2006)
The present article is a terminological reflection on lexical units within substantival syntagmes, such as idioms, collocations and compound nouns. A short introduction on polylexical units on the N+Adj model underlines the variety of possible terminological confusions, and puts forward a new criterion aiming at defining the peculiar linguistical status of polylexical units. It is necessary indeed to take the duality of the reference and actualization levels into consideration.